Planet of Snail - Seung-Jun, Yi (South Korea : Min-Chul, Kim ; Gary, Kam, 2011)
Young-Chan has been deaf and blind since childhood. As he puts it, "In the beginning there was darkness and silence." Young-Chan had no idea how to participate in the world until he meets Soon-Ho, who also has a physical handicap. He marries her and learns to communicate with the outside world through her. By softly tapping each other's finger, they can understand one another; sometimes it is as if they are tenderly playing a piano. This documentary follows the couple in the same gentle tempo as Young-Chan moves through his life. We see them replacing a light bulb together, receiving friends, working on a theater piece, reading a book, and gliding on a sleigh down a mountain. These everyday scenes are accompanied by a poetic voice-over by Young-Chan, in which he reflects on his existence without sight and hearing. He feels like an astronaut, but that doesn't mean he is without a sense of beauty in the world. This becomes palpable when Young-Chan touches the bark of a tree, runs his hand through sand, or brushes raindrops on a window pane with his fingertips. A unique testimony of love and the will to overcome obstacles.
Verzio Film Festival Submission
Duration: 01:27:00
Verzio Film Festival Submission
Keywords: Documentary films